Pattern and Presentation of Hepatocellular Carcinoma - Muhammad Sibtain Shah,1 Abdul Aziz Sahito2, Nasrullah Aamer,3 Rafique Ahmed Memon,4 Mir Tahir Hussain,5Abdul Manan Soomro,6 Abdul Jabbar Kandhro7 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2019)
Objective: To describe clinical pattern and presentation of Hepatocellular Carcinoma. Methods: This cross sectional study was conducted in Medical unit I,II,III ,Peoples University Of Medical and Health Sciences Nawabshah from January 2018 to June 2019.All consecutive patients suspected of having hepatocellular carcinoma, were included in this study.Diagnosis of hepatocellular carcinoma was established by clinical,biochemical,multiphasic CT scan abdomen.Patients were staged according Barcelona Clinic Liver Cancer (BCLC) staging system.We have excluded cases having hepatic metastasis from other sites to liver,e.g GIT tumors,carcinoma of lung,carcinoma of breast and tumors of genitourinary system.All demographic and clinical data was collected on a proforma.Data was statistically analyzed. Results:There were 100 patients with hepatocellular carcinoma including 62 males and 38 females.Most of patients were above 45 years of age.The right hypochondrial pain was major symptom in 61 patients,mass in right hypochondrial region 48 patients,abdominal distention 41 patients,jaundice 14 patients,weight loss 11 patients and altered consciousness 04 patients.Patients ECOG performance status from grade 0 to IV was 02,14,30,43,11 respectively.According to BCLC staging system 03 patients have stage 0, 09 patients have stage A, 22 patients have stage B, 53 patients have stage C and 13 patients have stage D.Hepatitis B and C was positive in 33 and 54 patients respectively. While 13 patients were suffering from both hepatitis B & C. Conclusion: Early detection of hepatocellular carcinoma and appropiate management can significantly improve survival and quality of life.